2008
DOI: 10.1021/es071703k
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Air Quality Impacts from Prescribed Fires on an Urban Area

Abstract: On February 28, 2007, a severe smoke event caused by prescribed forest fires occurred in Atlanta, GA. Later smoke events in the southeastern metropolitan areas of the United States caused by the Georgia-Florida wild forest fires further magnified the significance of forest fire emissions and the benefits of being able to accurately predict such occurrences. By using preburning information, we utilize an operational forecasting system to simulate the potential air quality impacts from two large February 28th fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 42 publications
(45 reference statements)
0
60
0
1
Order By: Relevance
“…Wildfire plume ozone production can lead to areas far from the original source to be out of compliance with regulatory standards, demonstrating the importance to be able to accurately model ozone production (Hu et al, 2008;Jaffe and Wigder, 2012;Lu et al, 2016). Also, as described here, particles aged through transport show internal mixtures of nitrate, sulfate, and oxidized organics, which can lead to increased CCN activity .…”
Section: Discussionmentioning
confidence: 85%
“…Wildfire plume ozone production can lead to areas far from the original source to be out of compliance with regulatory standards, demonstrating the importance to be able to accurately model ozone production (Hu et al, 2008;Jaffe and Wigder, 2012;Lu et al, 2016). Also, as described here, particles aged through transport show internal mixtures of nitrate, sulfate, and oxidized organics, which can lead to increased CCN activity .…”
Section: Discussionmentioning
confidence: 85%
“…Previous literature has shown that biomass burning can influence downwind O 3 precursor concentrations and therefore O 3 production via increased VOCs, nitrogen compounds and/or CO (Andreae and Merlet, 2001;McKeen et al, 2002;DeBell et al, 2004;Hu et al, 2008;Monks et al, 2009). In the June 9-12, 2015 event, however, a lag existed between enhanced PM 2.5 and O 3 concentrations along the smoke plume trek (Figure 3).…”
Section: Discussionmentioning
confidence: 85%
“…This is lower than the 0.525-1.025 ppm CO enhancements observed during the Quebec fires of 2002 (DeBell et al, 2004), but by comparison those measurements only traveled approximately 1-2 days and 1000 km from the smoke source and were in a noncontemporary (greater) regional emissions environment. Hu et al (2008) emphasized the importance of VOC concentrations from biomass smoke on O 3 production in a winter O 3 event, showing that O 3 production was more dependent on VOCs than on NOx, the two primary precursors to ozone. In the June 2015 case there was evidence of VOCs tracking with the smoke plume.…”
Section: Carbon Monoxidementioning
confidence: 99%
See 2 more Smart Citations